2019
DOI: 10.1101/848705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of the ERF102 to ERF105 genes of Arabidopsis thaliana and their role in the response to cold stress

Abstract: 22The ETHYLENE RESPONSE FACTOR (ERF) genes of Arabidopsis thaliana form a large 23 family encoding plant-specific transcription factors. Here, we characterise the four 24 phylogenetically closely related ERF102/ERF5, ERF103/ERF6, ERF104 and ERF105 25 genes. Expression analyses revealed that these four genes are similarly regulated by 26 different hormones and abiotic stresses. Analyses of tissue-specific expression using 27 promoter:GUS reporter lines revealed their predominant expression in root tissues 28 in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…It is worth mentioning that AtERF108, which is closely related to PtrERF108 in A. thaliana, has been previously identified as a gene responsive to abiotic stresses, including salt and drought stresses (Krishnaswamy et al, 2011), implying that ERF108 genes of various plants are crucial for abiotic stress tolerance. In addition to PtrERF108, several ERFs have been reported to be involved in cold tolerance, including PtrERF109 of trifoliate orange (Wang et al, 2019), VaERF057 and VaERF092 of grape (Sun et al, 2016(Sun et al, , 2019, ERF102-ERF105 of A. thaliana (Illgen et al, 2020) and BpERF13 of birch (Lv et al, 2020). The present results and previous reports demonstrated that the ERFs are crucial players to coordinate cold stress response hold great potential for manipulating cold tolerance by means of genetic engineering.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is worth mentioning that AtERF108, which is closely related to PtrERF108 in A. thaliana, has been previously identified as a gene responsive to abiotic stresses, including salt and drought stresses (Krishnaswamy et al, 2011), implying that ERF108 genes of various plants are crucial for abiotic stress tolerance. In addition to PtrERF108, several ERFs have been reported to be involved in cold tolerance, including PtrERF109 of trifoliate orange (Wang et al, 2019), VaERF057 and VaERF092 of grape (Sun et al, 2016(Sun et al, , 2019, ERF102-ERF105 of A. thaliana (Illgen et al, 2020) and BpERF13 of birch (Lv et al, 2020). The present results and previous reports demonstrated that the ERFs are crucial players to coordinate cold stress response hold great potential for manipulating cold tolerance by means of genetic engineering.…”
Section: Discussionsupporting
confidence: 73%
“…In addition to PtrERF108 , several ERFs have been reported to be involved in cold tolerance, including PtrERF109 of trifoliate orange (Wang et al., 2019), VaERF057 and VaERF092 of grape (Sun et al., 2016, 2019), ERF102‐ERF105 of A . thaliana (Illgen et al., 2020) and BpERF13 of birch (Lv et al., 2020). The present results and previous reports demonstrated that the ERFs are crucial players to coordinate cold stress response and hold great potential for manipulating cold tolerance by means of genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…ERF104 is also induced within minutes in response to abiotic stresses that require growth arrest (Moore, Vogel, and Dietz 2014; Vogel et al 2014; Illgen et al 2020), suggesting that it functions more generally in rapid stress adaptation than specifically in PTI activation. Indeed, despite their association with seemingly distinct biological processes (abiotic stress, biotic stress, stem cell functions), a common denominator of functions of many C5 transcription factors may be growth restriction as a general response to stress.…”
Section: Resultsmentioning
confidence: 99%
“…HSFA4A, HSFB2A, CAMTA3 (At2g22300), CAMTA6 (At3g16940), ANAC062 (At3g49530), MYB74 (At4g05100), and several ERFs (Doherty et al 2009; Vogel et al 2014; Yang et al 2014; Moore, Vogel, and Dietz 2014; R. Xu et al 2015; Guo et al 2016; Jacob et al 2018; Illgen et al 2020)), underscoring the multi-faceted reprogramming from growth and division to arrest immediately upon PAMP perception. Several additional transcription factors such as the Zinc finger/Homeobox factors HB4 (At2g44910) and HB28 (At3g50890) and the cytokinin response factor CRF5 (At2g46310, (Rashotte et al 2006)) have not previously been associated with defence responses, and their inclusion in C5 therefore opens new venues to investigate their biological functions.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of ERF105 is induced in response to paraquat in A. palmeri, and repressed in response to glyphosate in A. thaliana (Doğramacı et al, 2015;Illgen, Zintl, Zuther, Hincha, & Schmülling, 2020) Ferredoxin, NADPH reductase AT5G66190 (Gleason, Foley, & Singh, 2011) YABBY transcription factor AT2G45190 Mediates stress responses and flower/leaf development (Yang et al, 2018) 445…”
Section: Encoded Protein(s)mentioning
confidence: 99%